Jean-Jacques Rousseau : die beiden Diskurse zur Zivilisationskritik : Erster Diskurs über die Wissenschaften und die Künste (1750) ; Zweiter Diskurs über die Ungleichheit (1755) - Rohbeck, Johannes; Steinbrügge, Lieselotte (Klassiker auslegen, 2015)
This volume includes a step-by-step textual commentary on Jean-Jacques Rousseau's first and second critical discourses on civilization. Rousseau's thesis is that man has become progressively alienated from his own nature and thus perverted by technological and scientific progress. The example of Rousseau shows that critical reflection on modern civilization had already begun during the Enlightenment.